Honos alit artes. Studi per il settantesimo compleanno di Mario Ascheri. III. Il cammino delle idee dal medioevo all'antico regime Diritto e cultura nell'esperienza europea - Paola Maffei (Reti Medievali E-Book, 2014)
The essays gathered in the volume, thanks to a long series of in-depth studies, have resulted in a closer look at many crucial milestones in the history of European legal and political philosophy, both from the perspective of the common "ius commune" (civil and canon) and in particular rights of the individual jurisdictions. Analysis of strictly theoretical aspects are analyzed along with reviews on the subject of specific and concrete experiences; also stories from books and texts have been analyzed as elements of solicitation of cultural debate.